Impact Factors of Kualanamu International Airport Service Quality on Domestic Passenger Satisfaction - Lusi Laura Pasaribu; Rulianda Purnomo Wibowo; Isfenti Sadalia (International Journal Reglement & Society (IJRS), 2023)
The purpose of this study was to find out which service dimensions influence passenger satisfaction, from the Tangible variables (physical evidence), Reliability (reliability), Responsiveness (responsiveness), Assurance (guarantee) and Empathy (empathy) whether they jointly have an influence significant effect on passenger satisfaction, and what variable has the most dominant influence on passenger satisfaction at Kualanamu International Airport. This study uses a quantitative descriptive method. The population of the study were passengers at Kualanamu International Airport, with a total sample of 150 respondents. The data collection technique used the questionnaire method which was measured with a Likert scale of 1-5 with analysis techniques for validity and reliability tests, and multiple linear regression. From multiple regression analysis it can be concluded that the Reliability Factor has a regression coefficient value of 0.342 with a significance value of 0.010, and (Collateral) Assurance has a regression coefficient value of 0.337 with a significance value of 0.014. these three variables are the most influential factors on the level of passenger satisfaction at Kualanamu International Airport. The results of the calculations together obtained the calculated F value of 3.996 with a significance value of 0.005. Then the variable Reliability (Reliability) has the most dominant effect on customer satisfaction.